EFFECT OF HERBICIDE ON SPORULATION AND INFECTIVITY OF VESICULAR ARBUSCULAR MYCORRHIZAL (GLOM US MOSSEAE) SYMBIOSIS WITH PEANUT - A. Pasaribu; R. B. Mohamad; A. Hashim; Z. A. Rahman; D. Omar; Md. M. Morshed (Journal of Animal and Plant Sciences, 2013)
Arbuscular mycorrhizal fungi are of interest for their reported roles in preserving soil fertility in agroecosystem, which form mutualistic symbiosis with the roots of most agricultural plants. In the past, most research on VA mycorrhizae has been focused on possible responses to fungicides, rather than on the potential effects on mycorrhizal symbiosis following herbicide application. We studied the effect of three application rates of two widely used herbicides (1.8, 3.6 and 5.4 µg a.i. g-1 for alachlor and 1.08, 2.16 and 3.24 µg a.i. g-1 for glyphosate) on sporulation and infection of peanut plant by G mosseae under greenhouse conditions. The result of the study showed that the symbiont fungus G mosseae responds in a differential way to two different herbicides tested, and the fungus sensitivity to alachlor proved significantly higher than the glyphosate. However, none of the herbicide treatments affected the external hyphal length and SDH (Succinate dehydrogenase) activity. But the spore number, total and active infection intensity of internal hyphae was significantly reduced with the increasing rates of alachlor application, while glyphosate had no significant effects at all application rates. Consequently, P (phosphorus) inflow through mycorrhizal hyphae was significantly increased with the application rates of glyphosate, with the highest value (41.48 and 479.72 x10-13 mol P m-1 s -1 hyphal inflow and hyphal uptake, respectively) obtained at field recommended glyphosate rate (2.16 µg a.i. g-1). Therefore, symbiotic functions of G mosseae with host plant could be affected by the depressive effects of herbicides that are apparently related to the types of herbicide and their rates of application.
Keywords: Herbicidal toxicity; mycorrhizae; spore germination; infection intensity; G mosseae; peanut plant